2017
DOI: 10.1363/43e4317
|View full text |Cite
|
Sign up to set email alerts
|

Son Preference and Family Limitation in Pakistan: A Parity- and Contraceptive Method–Specific Analysis

Abstract: The association of son preference with parity progression and modern contraceptive use has become stronger in Pakistan. Continuation of the fertility transition may be difficult unless the degrees of differential stopping behavior and differential contraceptive use decline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 25 publications
2
19
0
Order By: Relevance
“…The tradition of son preference and its implications has been described in many cultures and countries [25, 26]. The findings of our study corroborate the narrative that son preference continues to be an issue in many country settings [27, 28]. Son preference could be a deciding factor in women’s health as they have been shown to influence fertility and reproductive behavior [29, 30].…”
Section: Discussionsupporting
confidence: 86%
“…The tradition of son preference and its implications has been described in many cultures and countries [25, 26]. The findings of our study corroborate the narrative that son preference continues to be an issue in many country settings [27, 28]. Son preference could be a deciding factor in women’s health as they have been shown to influence fertility and reproductive behavior [29, 30].…”
Section: Discussionsupporting
confidence: 86%
“…Our findings indicated that fertility preferences (ideal number of children and ideal number of boys) were not associated with the uptake of female sterilization by women of reproductive age. This finding partly disagrees with those of earlier studies such as in Uganda where contraceptive use among women is partly hindered by patriarchal family units that highly value children and encourage large family sizes [6], Ethiopia where the desire for no more children by women was significantly associated with women's demand for long acting and permanent methods in [39], Zambia where women whose husbands desired more children were less likely to use modern contraceptive methods including female sterilization [30] and Pakistan where permanent method use among women was significantly associated with the number of sons they had ever born [40].…”
Section: Discussionmentioning
confidence: 99%
“…The fertility behaviour exhibited by Turkish immigrant women in Germany therefore mimics that displayed by immigrant women hosted in industrialized societies who originate from son-preferring societies and adopt the son-preferring fertilitystopping rule. For example, like Pakistani women in their native country who use the son-preferring fertility-stopping rule to ensure the birth of at least one son, immigrant women of Pakistani origin in Canada and the United States continue to adopt this rule towards the same end (Adamou, Drakos, and Iyer 2013;Almond, Edlund, and Miligan 2013;Channon, 2017).…”
Section: Discussionmentioning
confidence: 99%